Implicit manifestation of prospective metacognition in betting choices enhances its efficiency compared to explicit expression - Nagamura, Hidekazu; Onishi, Hiroshi; Kobayasi, Kohta I.; Yuki, Shoko (Frontiers in Human Neuroscience, 2025)
Recent metacognitive research has extensively investigated metacognitive efficiency (i.e., the accuracy of metacognition). Given the functional importance of metacognition for adaptive behavioral control, it is important to explore the nature of prospective metacognitive efficiency; however, most research has focused on retrospective metacognition. To understand the nature of prospective metacognition, it is essential to identify the factors that influence its efficiency. Despite its significance, research exploring the factors of prospective metacognitive efficiency remains scarce. We focused on the relationship between the efficiency of prospective metacognition and the manner in which metacognition is inferred. Specifically, we explored whether explicit metacognition based on verbal confidence reports and implicit metacognition based on bets produce differences in efficiency. Participants were instructed to either respond to a memory belief with a sound (explicit metacognition) or make a bet on its recallability (implicit metacognition) during a delayed match-to-sample task. The task was identical for all participants, except for the pre-rating instructions. We found that the efficiency of prospective metacognition was enhanced by the betting instructions. Additionally, we showed the possibility that this difference in metacognitive efficiency was caused by the difference in pre-rating variability between the instructions. Our results suggest that the way a person evaluates their own internal states makes the difference in the efficiency of prospective metacognition. This study is the first to identify a factor that regulates the efficiency of prospective metacognition, thereby advancing our understanding of the mechanisms underlying metacognition. These findings highlight that the potential influence of framing, such as instruction, can improve metacognitive efficiency.